1999
DOI: 10.1111/j.1540-8167.1999.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Programmed Ventricular Stimulation in Patients with Congenital Heart Disease

Abstract: VSTIM in a large, selected group of congenital heart disease patients identified a subgroup with significantly increased mortality and sudden arrhythmic events. Failure to induce VT was a favorable prognostic sign, but the frequency of false-negative studies was high. Frequent supraventricular tachycardia further complicated risk stratification. Although VSTIM appears to be a reasonable tool for evaluation of this population, a larger, multicenter trial is recommended to clarify its utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…Although not assessed in the present study, inducible nonsustained VT has also been associated with decreased survival in a mixed cohort of congenital heart patients. 10 Although the value of inducible VT as a risk factor after tetralogy of Fallot repair has been demonstrated, questions about patient selection for screening and the timing and frequency of testing remain to be elucidated. Test sensitivity, specificity, and likelihood ratios, increasingly considered the best available indexes to evaluate diagnostic tests, are independent of prevalence assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Although not assessed in the present study, inducible nonsustained VT has also been associated with decreased survival in a mixed cohort of congenital heart patients. 10 Although the value of inducible VT as a risk factor after tetralogy of Fallot repair has been demonstrated, questions about patient selection for screening and the timing and frequency of testing remain to be elucidated. Test sensitivity, specificity, and likelihood ratios, increasingly considered the best available indexes to evaluate diagnostic tests, are independent of prevalence assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators found that patients with low-grade ectopy (isolated beats or couplets) were less likely to have inducible VT than patients with high-grade ectopy (sustained or nonsustained VT). Furthermore, patients with inducible VT had a higher risk of sudden cardiac death, although there were many false negatives (12). Khairy et al (13) reported a multicentre study that examined the prognostic role of VSTIM in repaired tetralogy of Fallot patients in which inducible sustained VT predicted an increased risk of clinical VT or sudden cardiac death.…”
Section: Cardiac Tumours and Icdsmentioning
confidence: 99%
“…The role of programmed ventricular stimulation (VSTIM) to assess risk of mortality in this group of patients is also unclear. Alexander et al (12) used VSTIM in selected patients with palliated or repaired congenital heart disease, including tetralogy of Fallot, aortic stenosis and dextro-transposition of the great arteries. The investigators found that patients with low-grade ectopy (isolated beats or couplets) were less likely to have inducible VT than patients with high-grade ectopy (sustained or nonsustained VT).…”
Section: Cardiac Tumours and Icdsmentioning
confidence: 99%
“…However, the distinction between what is normal and abnormal in terms of VT inducibility has not yet been clearly substantiated (1,12,13). The susceptibility to inducible VT may be influenced by a variety of factors in addition to genotype, including age, sex, strain, and autonomic and catecholaminergic state.…”
mentioning
confidence: 99%